EMOTION REGULATION IN RELATION TO ADOLESCENT PROSOCIAL BEHAVIOR IN TERMS OF GENDER - Handayani, Wiwik; Suroso, Suroso; Pratitis, Niken Titi; Pereira, Maria; Saeed, Aishath (International Journal of Research in Counseling, 2025)
There are several stories in the media, reported a decline in prosocial behavior and a tendency for people to behave impatiently. The aims of this research was to determined the corelations between Emotion Regulation and Prosocial Behavior concerning the students of Vocational High School (SMK), in terms of gender. Research was conducted by asking questions to students, with a number of statements that had been prepared. Subjects were students at the Surabaya Pharmacy Vocational School. The number of samples pick up with simple random sampling technique/ Questionaires about the Emotion Regulation Scale, and the Prosocial Behaviors Scale. Meanwhile with the Spearman correlation method, it was found that "There is a significant corelation between Emotion Regulation and Prosocial Behaviors". Furthermore, it can be concluded that Emotion Regulation makes an effective contribution to Prosocial behavior. There is no significant difference between Prosocial Behaviors of male and female student